Brain Angiotensin II Type 1 Receptor Blockade Improves Dairy Blood Pressure Variability via Sympathoinhibition in Hypertensive Rats - Takuya Kishi; Yoshitaka Hirooka; Kenji Sunagawa (International Journal of Hypertension)
Abnormal blood pressure (BP) elevation in early morning is known to cause cardiovascular events. Previous studies have suggested that one of the reasons in abnormal dairy BP variability is sympathoexcitation. We have demonstrated that brain angiotensin II type 1 receptor (AT1R) causes sympathoexcitation. The aim of the present study was to investigate whether central AT1R blockade attenuates the excess BP elevation in rest-to-active phase in hypertensive rats or not. Stroke-prone spontaneously hypertensive rats (SHRSP) were treated with intracerebroventricular infusion (ICV) of AT1R receptor blocker (ARB), oral administration of hydralazine (HYD), or ICV of vehicle (VEH). Telemetric averaged mean BP (MBP) was measured at early morning (EM), after morning (AM), and night (NT). At EM, MBP was significantly lower in ARB to a greater extent than in HYD compared to VEH, though MBP at AM was the same in ARB and HYD. At NT, MBP was also significantly lower in ARB than in HYD. These results in MBP were compatible to those in sympathoexcitation and suggest that central AT1R blockade attenuates excess BP elevation in early active phase and continuous BP elevation during rest phase independent of depressor response in hypertensive rats.